A High Throughput Assay for Screening Host Restriction Factors and Antivirals Targeting Influenza A Virus - Wang, Lingyan; Li, Wenjun; Li, Shitao (Frontiers in Microbiology, 2016)
IInfluenza A virus (IAV) is a human respiratory pathogen that causes seasonal epidemics and occasional global pandemics with devastating levels of morbidity and mortality. Currently approved treatments against influenza are losing effectiveness as new viral strains are often refractory to conventional treatments. Thus, there is an urgent need to find new therapeutic targets with which to develop novel antiviral drugs. The common strategy to discover new drug targets and antivirals is high throughput screening. However, most current screenings for influenza A virus rely on the engineered virus carrying a reporter, which prevents the application to newly emerging wild type flu viruses, such as 2009 pandemic H1N1 flu. Here we developed a simple and sensitive screening assay for wild type influenza A virus by quantitatively analyzing viral protein levels using a Dot Blot Assay in combination with the LI-COR Imaging System (DBALIS). We first validated DBALIS in overexpression and RNAi assays, which are suitable methods for screening host factors regulating viral infection. More importantly, we also validated and initiated drug screening using DBALIS. A pilot compound screening identified a small molecule that inhibited influenza A virus infection. Taken together, our method represents a reliable and convenient high throughput assay for screening novel host factors and antiviral compounds.